RELATIONSHIP OF EMOTIONAL INTELLIGENCE WITH ELEMENTARY SCHOOL STUDENTS 'CRITICAL THINKING ABILITY - Septiana, Putri; Purwanti, Eko (Universitas Negeri Semarang, 2020)
This research aidmed to exame the correlation between emotional intelligence to students' critical thinking skills of 4th grade students in elementary school, Cepiring Subdistrict, Kendal Regency. This research used quantitative method correlation design. The subjects of this research were 4th grade students. The research sample of 132 participants was taken by using a purpossive sampling. Data collection used interview, test, questionnaire, documentation, and observation. Data analysis techniques used descriptive statistic, prerequisite test, and hypothesis test. The result of the research showed there are positive and significant correlation between emotional intelligence with students' critical thinking skills; coefficient correlation 0.643 included strong category.